Technical, Economic, and Environmental Assessment of the Hydrothermal Carbonization of Green Waste. Issue 2 (20th December 2016) - Zeymer, Martin; Meisel, Kathleen; Clemens, Andreas; Klemm, Marco
Abstract: The attempt to transition from a fossil‐based to a bio‐based economy is putting increased pressure on the limited amount of available biomass. Concentrating on biogenic waste matter that is currently not put to use, such as green waste, may be one way of tapping potential additional raw materials. Hydrothermal carbonization (HTC) processes are particularly well suited for converting this green waste into valuable energy sources. The results show that HTC coal can currently only compete economically with fossil energy sources in an ideal context. However, there is potential for cost reduction. Additionally, there is a clear potential for reducing greenhouse gas (GHG) emissions compared with fossil fuels and the GHG mitigation costs are within the standard range of other biogenic means of supplying heat. Abstract : Since moist biomass is a largely untapped resource for renewable energy generation, five green waste‐based HTC coal production and heating concepts were defined through technological analysis. In order to determine the most advantageous concept from an economic and environmental point of view, the levelized cost of energy and the carbon footprint as part of life‐cycle assessment were determined.